Effects of Mineralocorticoid Receptor Overexpression on Anxiety and Memory after Early Life Stress in Female Mice - Kanatsou, Sofia; Ter Horst, Judith P.; Harris, Anjanette P.; Seckl, Jonathan R.; Krugers, Harmen J.; Joëls, Marian (Frontiers in Behavioral Neuroscience, 2016)
Early-life stress is a risk factor for the development of psychopathology, particularly in women. Human studies have shown that certain haplotypes of NR3C2, encoding the mineralocorticoid receptor (MR), that result in gain of function, may protect against the consequences of stress exposure, including childhood trauma. Here, we tested the hypothesis that forebrain-specific overexpression of MR in female mice would ameliorate the effects of early-life stress on anxiety and memory in adulthood. We found that early-life stress increased anxiety, did not alter spatial discrimination and reduced contextual fear memory in adult female mice. Transgenic overexpression of MR did not alter anxiety but affected spatial memory performance and enhanced contextual fear memory formation. The effects of early life stress on anxiety and contextual fear were not affected by transgenic overexpression of MR. Thus MR overexpression in the forebrain does not represent a major resilience factor to early life adversity in female mice.